System on Chip (SOC)-FPGA for multimode vehicle data communication - Aris, Ishak; Kamsani, Noor 'ain; Abdul Halin, Izhal (2024)
A method of manufacturing a high electron mobility transistor (1), said method comprising the steps of: − providing a target wafer (10) comprising a target substrate (100); − providing a donor wafer (20) comprising an epitaxial donor film (21); − bonding said donor film (21) to said target wafer (10); − separating said donor wafer (20) and said target wafer (10) along said first donor III-N layer (201), thereby forming on said target wafer (10) a top surface layer (221) of 200nm or less; − epitaxially growing an epitaxial III-N semiconductor layer stack (300) on top of said top surface layer (221); − forming a gate contact (41) in a gate region (401); and − forming a substrate galvanic contact (42) contacting said target substrate (100).